The recycling of biodigested vinasse in an upflow anaerobic sludge blanket reactor is a feasible approach for the conservation of freshwater in the biofuel ethanol industry - Madaleno, Leonardo Lucas; Barros, Valciney Gomes de [UNESP]; Kesserling, Mayara Aparecida; Teixeira, Josiene Rocha; Duda, Rose Maria [UNESP]; Oliveira, Roberto Alves de [UNESP] (Elsevier, 2020)
The generation of large volumes of vinasse during the production of biofuel ethanol is a challenging problem since inappropriate application of the byproduct as an agro-fertigant can give rise to contamination of soil and watercourses and cause harm to aquatic life. The aims of the study were(i) to evaluate an alternative strategy involving the generation of biogas by anaerobic digestion of sugarcane vinasse in two-stage upflow anaerobic sludge blanket (UASB) reactors (R1 and R2 connected in series), and (ii) to determine the ethanol content and fermentation efficiency of mashes prepared by diluting sugarcane molasses with deionized water, fresh vinasse and effluents from R1 or R2, both before and after submission to the Fenton reaction. The highest percentages of ethanol were obtained with fermentation mashes prepared from molasses diluted with Fenton-treated R1 (5.1%) or R2 effluents (5.7%) or with non-treated R2 effluent (5.7%). The corresponding fermentation efficiencies of these processes were 88.5, 92.1 and 89.3%. The proposed combination of biofuel and biogas production would provide a sustainable source of energy, contribute to the safe disposal of large quantities of vinasse and help to reduce the volume of freshwater employed by the sugarcane processing industry.
Keywords: Anaerobic digestion; Biogas; Sugarcane molasses; Sugarcane vinasse; Wastewater reuse; Water conservation